2015
DOI: 10.1371/journal.pone.0144309
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Hypertrophy and Increased Susceptibility to Spontaneous Calcium-Release of Rat Left Atrial Myocytes Due to Elevated Afterload

Abstract: Atrial remodeling due to elevated arterial pressure predisposes the heart to atrial fibrillation (AF). Although abnormal sarcoplasmic reticulum (SR) function has been associated with AF, there is little information on the effects of elevated afterload on atrial Ca2+-handling. We investigated the effects of ascending aortic banding (AoB) on Ca2+-handling in rat isolated atrial myocytes in comparison to age-matched sham-operated animals (Sham). Myocytes were either labelled for ryanodine receptor (RyR) or loaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
2
15
0
4
Order By: Relevance
“…Moreover, the increase in current density produced by inhibition of serine/threonine protein phosphatase activity with calyculin A provides evidence of phosphorylation-dependent basal regulation of I CaL in both groups of cells. In these respects, the data resemble those reported by Dinanian et al in human atrial myocytes from patients with heart failure (19) and by Boixel et al in a model of coronary artery ligation-induced heart failure in rats similar to that used in the present study (4) and contrast with studies of chronic hypertension and pressure overload in rats that show a reduction in atrial ␣ 1c subunit protein expression (38,51). However, contrary to the mechanism proposed by Boixel et al (4), the insensitivity of basal I CaL to H-89 and PKI in the present study demonstrated that protein kinase A did not contribute to the constitutive regulation of atrial I CaL .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the increase in current density produced by inhibition of serine/threonine protein phosphatase activity with calyculin A provides evidence of phosphorylation-dependent basal regulation of I CaL in both groups of cells. In these respects, the data resemble those reported by Dinanian et al in human atrial myocytes from patients with heart failure (19) and by Boixel et al in a model of coronary artery ligation-induced heart failure in rats similar to that used in the present study (4) and contrast with studies of chronic hypertension and pressure overload in rats that show a reduction in atrial ␣ 1c subunit protein expression (38,51). However, contrary to the mechanism proposed by Boixel et al (4), the insensitivity of basal I CaL to H-89 and PKI in the present study demonstrated that protein kinase A did not contribute to the constitutive regulation of atrial I CaL .…”
Section: Discussionsupporting
confidence: 89%
“…Evidence from animal models of heart diseases that predispose to AF indicates that disease-associated remodeling of the atria, presumably due to mechanical overload of the atrial wall, creates an arrhythmic substrate in which AF is more likely to arise and be sustained (10,13,22,29,30,32,34,48). In addition to atrial enlargement, fibrosis and conduction abnormalities that establish a substrate for reentry, cellular remodeling involving cellular hypertrophy, changes in membrane structure, and abnormal expression and function of ion channels and transporters are also likely to contribute to the genesis of AF (4,10,13,15,16,18,22,26,29,30,32,34,35,38,48,51).…”
Section: New and Noteworthy Whole Cell Recording Of L-type Ca 2ϩmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In a rat model hypertrophic LA myocytes had a high arrhythmogenic potential with greater incidence and frequency of spontaneous Ca 2+ -transients. 20 Connexin Modification Gap junctions are composed of narrow membrane channels that permit small molecules to diffuse intercellularly. In rat ventricular cardiomyocytes, gap junctions provide low-resistance electrical coupling between adjacent cardiac myocytes.…”
Section: Effects Of Aging On Electrophysiological Remodelingmentioning
confidence: 99%
“…Third, a stretch of cardiac myocytes causes the activation of ion channels that induce increased Ca 2+ influx, which may in turn activate downstream pathways and serve as an intracellular signal of hypertrophy and gene regulation (31). In addition, stretch of cardiac myocytes increases the concentration of Ang II and ET-1 in the conditioning medium and stimulates protein synthesis and gene expression associated with mitogen-activated protein Kinase activity (32).…”
Section: Discussionmentioning
confidence: 99%